Namūdzaju Ikhtibārāt al-Lughati li at-Tarjamati al-‘Arabiyyati ‘alā Asāsi Nadhariyyati Bloom - Ihwan Mahmudi; Annisa Fithri Lathiifah; Sumayyah Alifatun Qanita (Universitas Negeri Malang, 2023)
This study aims to determine the language test model in lecture material based on Bloom's Taxonomy theory which is used to measure the success or failure of the educational process. This research is also aimed at looking at the progress of translation studies and language skills between the mother tongue and the target language, such as article translation, translation correction, interpretation and special translation. This study used a library research design and note-taking techniques. This research method uses aspects of library research with literacy data sources related to the language test model in lecture materials based on Bloom's Taxonomy theory. The results of the analysis show that the types and classifications of tarjamah test material on bloom theory are effective tools for improving the learning process and encouraging students to progress, and can be a means for evaluating students' linguistic performance. In this test there are several types of translation tests, namely translation from the mother tongue into the target language and vice versa, general translation and special translation. The classification of the test according to Bloom aims to determine the ability of each student. تهدف هذه الدراسة إلى تحديد نموذج اختبار اللغة في مادة الترجمة بناءً على نظرية تصنيف بلوم التي تستخدم لقياس نجاح أو فشل العملية التعليمية. يهدف هذا البحث أيضًا إلى النظر في تقدم دراسات الترجمة والمهارات اللغوية بين اللغة الأم واللغة الهدف، مثل ترجمة المقالات وتصحيح الترجمة والترجمة الفورية والترجمة الخاصة. واستخدمت الباحثة هذه الدراسة بحث المكتبة وتقنيات تدوين الملاحظات. استخدمت الباحثة منهج البحث المكتبات مع مصادر بيانات محو الأمية المتعلقة بنموذج اختبار اللغة في مادة الترجمة بناءً على نظرية تصنيف بلوم. تظهر نتائج التحليل أن أنواع وتصنيفات مادة اختبار الترجمة على نظرية بلوم هي أدوات فعالة لتحسين عملية التعلم وتشجيع الطلاب على التقدم، ويمكن أن تكون وسيلة لتقييم الأداء اللغوي للطلاب. يوجد في هذا الاختبار عدة أنواع من اختبارات الترجمة، وهي الترجمة من اللغة الأم إلى اللغة الهدف والعكس بالعكس والترجمة العامة والترجمة الخاصة. يهدف تصنيف الاختبار حسب بلوم إلى تحديد قدرة كل طالب